The Human Health under the Complex Environmental Impact - Olga M. Stupishina; Elena G. Golovina; Sergei N. Noskov; Gennadiy B. Yeremin; Sergei A. Gorbanev (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 5, 2023)
The paper combines the conclusions of two works [1,2] and proposes the investigation’s results of helio-geo-physical and meteorological variations those were matching the different cardio-events. Two data arrays of such cardio-events on the territory of Saint Petersburg, Russia in different time intervals were studied. The first data array contains 15,120 ischemia cases from the call logs of the medical officials in one of Saint Petersburg’s districts in 2006-2009 years (the fall branch of 23rd solar activity cycle and the minimum of the solar activity). We have analyzed the Terrestrial and Space Weather characteristics in days with normal for the concrete calendar seasons numbers of ischemia cases vs. days which were absolutely free of same cases. The second data array contains the cardio-events those were selected from the logs of 6 Saint Petersburg’s medical state establishments in Summer, 2002 (close to the maximum of 23rd solar activity cycle), the aggregate number of these cardio-events is 1,381. For these data we have analyzed the mentioned above environmental characteristics in days with normal for Summer, 2002 number of cardio-catastrophes vs. absence of them. For the data treatment we have used some elements of the Folder Epochs method, some elements of Cluster Analysis and the Mann–Whitney hypothesis test criterion. The findings show the difference in the behavior of the geomagnetic field daily spread at the altitude of the geostationary orbit before the days of the different cardio-events registration as well as the spread of the relative humidity for the days when cardio-events absent in any phase of the solar activity cycle. The importance of solar activity manifestations in the solar activity cycle phase that is close to maximum is shown.